Door Access System via Fingerprint with GSM (ReSMART) - Muhamad Hafizuddin, Afiq Anuar; Noorlin, Mohd Ali; Al-Fahim, Mubarak-Ali; Syahrulanuar, Ngah (Penerbit Universiti Malaysia Pahang, 2016)
This work presents the prototype of door access system using biometric authentication (fingerprint) (ReSMART) for highly-protected area. The implementation of password authentication or ordinary key is somehow having the issues on security risk; therefore we propose ReSMART to enhance the process. ReSMART will verify the fingerprint of registered user, once the authentication is passed, the system will notify the authorized personal of door access activity through short message service (SMS).